Listening for a Life - Swain, Patricia (Utah State University, University Libraries, 2004)
In one sense a folklorist's portrayal of a notable folk artist's life and art, Listening for a Life is equally a rethinking of the processes involved in such work, not only in how the folklorist conveys her subject but in how her subject constitutes and performs herself into being through dialogue with others: those present, those once present, those imagined and anticipated.Drawing on Bahktinian and feminist theory, Sawin pushes forward our understanding of the interactive roles of ethnographer and subject and in the process gives us a deeper understanding of folk singer and storyteller Bessie Eldreth and her greatest art, herself.